(untitled) (The Review of Diabetic Studies, 2025)
Background: Lower-limb joint replacement and anterior cruciate ligament (ACL) reconstruction are among the most common orthopedic surgeries requiring structured rehabilitation. This systematic review examined the role of physiotherapists across the recovery continuum—from prehabilitation to long-term recovery—and evaluated traditional and technology-assisted interventions. Methods: Following PRISMA 2020 guidelines, studies published between 2005 and 2024 were reviewed across six databases. Eligible studies included physiotherapist-led interventions before and after total hip/knee arthroplasty or ACL reconstruction. Results: Thirty studies (n=4,700+) demonstrated that physiotherapist-led rehabilitation significantly improved pain reduction, range of motion, strength, gait, and quality of life, with adherence rates above 80%. Prehabilitation enhanced surgical readiness, while postoperative and digital programs accelerated recovery and accessibility. Conclusion: Physiotherapists play a vital leadership role in recovery optimization, digital rehabilitation integration, and long-term functional independence. Standardized protocols and AI-based research are recommended for future practice.